022 Piloting home infusions of natalizumab: a randomised crossover trial. Issue 6 (24th May 2018) - Schultz, Tim; Thomas, Anne; Georgiou, Paul; Juaton, Mahasen; Simon, Lorraine; Cusack, Lynette; Naidoo, Kerisha; Webb, Kevin; Karnon, Jon; Ravindran, Janakan
Abstract : Introduction: For people with multiple sclerosis, monthly infusions at specialist clinics are time consuming, potentially costly and restrictive. Conversely, increased demand for hospital services is driving innovation, including delivery of care in the home. We developed a rigorous model of care for home infusions of natalizumab, which was evaluated in a randomised crossover trial. This pilot study (i) tested feasibility and safety of home infusions, and (ii) compared acceptability and clinical effectiveness with usual clinic-based care in a hospital outpatients clinic. Methods: We recruited 37 stable adult patients (at least 6 prior natalizumab infusions and assessed as safe by their neurologist) who were randomised to an AB or BA trial arm. After 3 infusions, patients crossed over to the alternate treatment for another 3 infusions. The following outcomes were assessed treatment adherence, patient safety outcomes, quality of life (Multiple Sclerosis Quality of Life Inventory, MSQLI), and patient satisfaction (Treatment Satisfaction Questionnaire for Medication, TSQM). Results: Two patients moved out of Adelaide and withdrew. No adverse events resulting from the infusion in either the home or clinic setting were reported. There was no difference between home and clinic in the adherence rate (86/104, 82.7% at home) and (84/103, 81.6% at clinic) (X 2 =0.0, p=1.0) and number of infections during home care 8 compared to clinic 10 (X 2 =0.04, p=0.84). There was no difference in any of the nine sub-scales of the MSQLI (p>0.05). Of the four sub-scales of the TSQM ('Effectiveness', 'Side effects', 'Convenience', 'Global satisfaction'), patients most recently receiving home care were significantly more satisfied with the Convenience of their treatment (p=0.0008). Conclusion: Data from the pilot study suggest that delivery of infusions of natalizumab at home is feasible, safe and as effective as the hospital setting. Patients reported that home infusions were more convenient than the clinic.